[Engraved Murals at School in Laugarvatn] - Streng, Evelyn Fiedler (1975)
Photograph of engraved murals along a school in Laugarvatn, Iceland. The brown murals sit in flat, white niches on a rectangular building. The mural to the left depicts a person sat on a stool, leaning over a table covered in books. To the right of that mural, another mural depicting a group of people forming a circle. The person on the bottom holds a circle in their hand. Red rock and dirt covers the bottom of the photograph.